2016
DOI: 10.12973/edupij.2016.52.2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Impulsivity, Social Media Usage and Loneliness

Abstract: The purpose of this study is to examine the relationships between impulsivity, social media usage, and loneliness and to test the structural hypothetical model developed based on the literature. The study was conducted on 307 (164 female, 143 male) university students. Data collection instruments of the study were the Barratt Impulsivity Scale Short Form (BIS-11-SF), Social Media Usage Scale (SMUS), and UCLA Loneliness Scale Short Form (ULS-8). The measurement models of the latent variables were tested initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 30 publications
(39 reference statements)
3
36
0
5
Order By: Relevance
“…Research have shown that internet addiction, social media addiction, smartphone addiction and digital game addiction are associated with "depression" (24)(25)(26)(27), "impulsivity" (7,(28)(29)(30), "loneliness" (31)(32)(33)(34), "sleep quality" (25,27,35,36), "well-being" (25,(37)(38)(39), "self-esteem" (33,34,40,41) and "academic performance" (24,(42)(43)(44). On the other hand, according to some researchers, the use of technology strengthens friendship, facilitates interpersonal conversations and communication, and allows establishing new social relations (45)(46)(47).…”
Section: Introductionmentioning
confidence: 99%
“…Research have shown that internet addiction, social media addiction, smartphone addiction and digital game addiction are associated with "depression" (24)(25)(26)(27), "impulsivity" (7,(28)(29)(30), "loneliness" (31)(32)(33)(34), "sleep quality" (25,27,35,36), "well-being" (25,(37)(38)(39), "self-esteem" (33,34,40,41) and "academic performance" (24,(42)(43)(44). On the other hand, according to some researchers, the use of technology strengthens friendship, facilitates interpersonal conversations and communication, and allows establishing new social relations (45)(46)(47).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, as a result of excessive Internet use, users have been identified as becoming isolated with an increase in their depression symptoms, a decline in social relationships, and a heightened risk of Internet addiction (Kraut et al, 1998;Nalwa & Anand, 2003;Savcı, 2016;Savci & Aysan, 2016;Weinstein & Lejoyeux, 2010;Whang, Lee, & Chang, 2003). Thus, along with the benefits of the Internet, excessive use of the Internet has been stressed as triggering certain psychosocial problems as well (İkiz, Savcı, Asıcı, & Yörük, 2015).…”
mentioning
confidence: 99%
“…Those who use social media excessively, tend to have problems with spending their time effectively or to plan ahead. These are characteristics they share with impulsive individuals (Savcı et al, 2016). That's probably why individuals with high impulsive tendencies use SNS more often (Wu et al, 2013).…”
Section: Propensity Theories and Impulsivitymentioning
confidence: 99%